Oral Tuberculosis: A Rare Manifestation of Disseminated Disease in a Patient with Dermatomyositis on Chronic Corticosteroids - Dina Khateeb; Mohleen Kang; Eugenio Capitle; Mirela Feurdean (Case Reports in Medicine)
Tuberculosis remains one of the leading causes of death around the world despite advancements in diagnostic testing and medical therapies. It commonly affects the lungs, but isolated extra pulmonary clinical manifestations have been reported. Tuberculosis of the oral cavity is exceedingly rare. We present a case of a patient with dermatomyositis on chronic steroid therapy, who presented with tuberculosis involving the tongue as the only clinical manifestation of disseminated disease. Physicians must be aware of extra pulmonary manifestations of tuberculosis in patients at risk, in order to avoid delays in diagnosis and treatment and to prevent further contagion.